The dispersal and adaptation of Homo sapiens onto the Tibetan Plateau during MIS 3: an Initial Upper Paleolithic assemblage from Nwya Devu? - Peiqi Zhang; Xiaoling Zhang; Linhui Li; Wei He; Yingshuai Jin; Junyi Ge; Shejiang Wang; Nicolas Zwyns; Xing Gao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Hydroclimate variability in Northeast China during Marine Isotope Stages 3-2 - Niankang Chen; Ting Xu; Shurun Li; Zeyuan Weng; Zhuoqun Rong; Dongmei Jie; Guizai Gao; Junyi Ge (Global and Planetary Change, 2026)

Population responses to climate change in the marginal areas of the dryland in East Asia since the LGM - Yanyan Yu; Junyi Ge; Junyan Geng; Haibin Wu; Amber Johnson; Feng He; Zhengtang Guo (Quaternary Science Reviews, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

New U-series and coupled ESR/U-series dating of Xujiayao (northern China), the type site for Homo juluensis - Qingfeng Shao; Fagang Wang; Junyi Ge; Jean-Jacques Bahain; Pierre Voinchet; Guilan Hu; Xinrui Jin; Rainer Grün; Christopher J. Bae; Xing Song (Quaternary Science Reviews, 2026)

Time-Resolved Oxidative Stress and Apoptosis in Murine Retina under Acute Hypobaric Hypoxia with Parallel Activation of the LIF–JAK–STAT3 Axis - Hao Wang; Qiang Ye; Songjian Huang; Keke Ge; Cong Han; Huan Xi; Junyi Qiao; Jingrong Feng; Peirun Wu; Yuhan Bao; Yi Yang; Wenfang Zhang (Molecular Neurobiology, 2026)

Mapping vegetation phenology and its response to climate change in Southwest China using solar-induced chlorophyll fluorescence - Feng Tang; Zhongxi Ge; Bohui Tang; Liuyang Fang; Zhen Zhang; Dong Fan; Junyi Chen; Xinming Zhu (Journal of Mountain Science, 2026)

Late Miocene paleo-seismic events and tectonic responses of the western Qinling Mountains recorded in aeolian deposits - Long Chen; Zhengtang Guo; Xin Zhou; Junyi Ge; Chaoqin Chen; Zhilin He (Science China Earth Sciences, 2025)

The earliest evidence for a microblade adaptation in the remote, high altitude regions of the Tibetan Plateau - Yingshuai Jin; Xiaoling Zhang; Shejiang Wang; Junyi Ge; Wei He; Wa Da; Yunyao Tan; Ziyi Yang; Christopher Morgan; Xing Gao (Science China Earth Sciences, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Optically stimulated luminescence dating of Paleolithic sites reveals population shifts in North China during the last glacial period - Junyi Ge; Xiao Sun; Yan Li; Chunxue Wang; Lishuang Sheng; Ke Hu; Jiequn Hua; Xiaoling Zhang; Faxiang Huan; Shixia Yang; John W. Olsen; Xing Gao; et al. (Global and Planetary Change, 2024)

New dating indicates intermittent human occupation of the Nwya Devu Paleolithic site on the high-altitude central Tibetan Plateau during the past 45,000 years - Junyi Ge; Xiaoling Zhang; Shejiang Wang; Linhui Li; Wei He; Yingshuai Jin; Peiqi Zhang; Bing Xu; Chenglong Deng; John W. Olsen; Zhengtang Guo; Xing Gao (Science China Earth Sciences, 2024)

Continuous cropping disorders of eggplants (Solanum melongena L.) and tomatoes (Solanum lycopersicum L.) in suburban agriculture: Microbial structure and assembly processes - Zufei Xiao; Changyi Lu; Zhiyong Wu; Xinyuan Li; Kai Ding; Zhe Zhu; Ruixia Han; Junyi Zhao; Tida Ge; Gang Li; Yong-Guan Zhu (Science of The Total Environment, 2024)

Reassessing the age of the Early Pleistocene Longgupo fauna, southern China: An updated magnetostratigraphic perspective - LU SUN; CHENGLONG DENG; CAICAI LIU; JUNYI GE; SHIXIA YANG; SHUAI ZHANG; FEI HAN; JEAN‐JACQUES BAHAIN; MICHEL RASSE; ÉRIC BOËDA; YAMEI HOU; GUANGBIAO WEI; et al. (Journal of Quaternary Science, 2023)
As the northernmost locality yielding one of the most representative Early Pleistocene Gigantopithecus – Sinomastodon faunas in southern China, the Longgupo site has preserved valuable geological archives that have significantly improved our understanding of Pleistocene biostratigraphy and biogeography. A convincing chronological framework of this locality is therefore important to elaborate on the evolution of Quaternary faunas as well as paleoenvironment. To reconcile the existing geochronological results with new advances in geochronology and biochronology, we present here a revised magnetostratigraphic age model based on detailed rock magnetic and paleomagnetic data and strengthened by biochronology as well as recently published electron spin resonance and uranium series (ESR/U‐series) age data. Two geomagnetic polarities were identified from the Longgupo sequence: the upper one is thin and normal, corresponding to the Olduvai normal subchron; and the lower one is distinctly thick and reversed, corresponding to the pre‐Olduvai Matuyama Chron. The age of the Longgupo fauna constrained by this refined magnetochronological framework is therefore estimated to be about 2.5–2.0 Ma, consistent with the newly published ESR/U‐series age of 2.5–2.2 Ma.

Decreasing summer monsoon precipitation during the Mid-Pleistocene transition revealed by a pollen record from lacustrine deposits of the Northeast Plain of China - Tao Zhan; Ye Yang; Yanxia Liang; Xiaoyan Liu; Fangming Zeng; Junyi Ge; Yongfa Ma; Keliang Zhao; Xinying Zhou; Xia Jiang; Rongfu Huang; Xun Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Climatic factors and human population changes in Eurasia between the Last Glacial Maximum and the early Holocene - Yanyan Yu; Feng He; Stephen J. Vavrus; Amber Johnson; Haibin Wu; Wenchao Zhang; Qiuzhen Yin; Junyi Ge; Chenglong Deng; Michael D. Petraglia; Zhengtang Guo (Global and Planetary Change, 2023)

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Evaluation of vulnerable PM2.5-exposure individuals: a repeated-measure study in an elderly population - Haiyan Chu; Junyi Xin; Qi Yuan; Xu Zhang; Wang Pan; Xinying Zeng; Yaoyao Chen; Gaoxiang Ma; Yuqiu Ge; Mulong Du; Na Tong; Xiaobo Li; et al. (Environmental Science and Pollution Research, 2018)

Metatranscriptomics analysis of cyanobacterial aggregates during cyanobacterial bloom period in Lake Taihu, China - Zhenzhu Chen; Junyi Zhang; Rui Li; Fei Tian; Yanting Shen; Xueying Xie; Qinyu Ge; Zuhong Lu (Environmental Science and Pollution Research, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Microbial profiles of a drinking water resource based on different 16S rRNA V regions during a heavy cyanobacterial bloom in Lake Taihu, China - Junyi Zhang; Congming Zhu; Rui Guan; Zhipeng Xiong; Wen Zhang; Junzhe Shi; Yi Sheng; Bingchuan Zhu; Jing Tu; Qinyu Ge; Ting Chen; Zuhong Lu (Environmental Science and Pollution Research, 2017)

The long persistence of pyrrolizidine alkaloid-derived DNA adducts in vivo: kinetic study following single and multiple exposures in male ICR mice - Lin Zhu; Junyi Xue; Qingsu Xia; Peter P. Fu; Ge Lin (Archives of Toxicology, 2017)

Inter- and intra-annual tree-ring cellulose oxygen isotope variability in response to precipitation in Southeast China - Chenxi Xu; Huaizhou Zheng; Takeshi Nakatsuka; Masaki Sano; Zhen Li; Junyi Ge (Trees, 2016)

Magnetostratigraphic evidence for deep-sea erosion on the Pacific Plate, south of Mariana Trench, since the middle Pleistocene: potential constraints for Antarctic bottom water circulation - Xiguang Deng; Liang Yi; Greig A. Paterson; Huafeng Qin; Haifeng Wang; Huiqiang Yao; Jiangbo Ren; Junyi Ge; Hongzhou Xu; Chenglong Deng; Rixiang Zhu (International Geology Review, 2016)

Elevation‐induced climate change as a dominant factor causing the late Miocene C 4 plant expansion in the Himalayan foreland - Haibin Wu; Zhengtang Guo; Joël Guiot; Christine Hatté; Changhui Peng; Yanyan Yu; Junyi Ge; Qin Li; Aizhi Sun; Deai Zhao (Global Change Biology, 2014)
During the late Miocene, a dramatic global expansion of C 4 plant distribution occurred with broad spatial and temporal variations. Although the event is well documented, whether subsequent expansions were caused by a decreased atmospheric CO 2 concentration or climate change is a contentious issue. In this study, we used an improved inverse vegetation modeling approach that accounts for the physiological responses of C 3 and C 4 plants to quantitatively reconstruct the paleoclimate in the Siwalik of Nepal based on pollen and carbon isotope data. We also studied the sensitivity of the C 3 and C 4 plants to changes in the climate and the atmospheric CO 2 concentration. We suggest that the expansion of the C 4 plant distribution during the late Miocene may have been primarily triggered by regional aridification and temperature increases. The expansion was unlikely caused by reduced CO 2 levels alone. Our findings suggest that this abrupt ecological shift mainly resulted from climate changes related to the decreased elevation of the Himalayan foreland.

Reconstructions of annual summer precipitation and temperature in north-central China since 1470 AD based on drought/flood index and tree-ring records - Liang Yi; Hongjun Yu; Junyi Ge; Zhongping Lai; Xingyong Xu; Li Qin; Shuzhen Peng (Climatic Change, 2012)

Thick Miocene eolian deposits on the Huajialing Mountains: The geomorphic evolution of the western Loess Plateau - Tao Zhan; ZhengTang Guo; HaiBin Wu; JunYi Ge; Xin Zhou; ChunLin Wu; FangMing Zeng (Science China Earth Sciences, 2011)